2009
DOI: 10.1177/0748233709346758
|View full text |Cite
|
Sign up to set email alerts
|

Effect of toluene on erythrocyte membrane stability under in vivo and in vitro conditions with assessment of oxidant/antioxidant status

Abstract: Toluene, an organic solvent used widely in the industry, is highly lipophilic and accumulates in the cell membrane impeding transport through it. Its metabolites cause oxygen radical formation that react with unsaturated fatty acids and proteins in erythrocytes leading to lipid peroxidation and protein breakdown. In this study, we aimed to investigate the membrane stabilizing and the oxidative stress-inducing effects of toluene in human erythrocytes. Measurements of osmotic fragility, mean corpuscular volume (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 20 publications
3
16
0
1
Order By: Relevance
“…Therefore, pravastatin can protect the erythrocytes NPSH against primaquine induced oxidation. These findings are in agreement with the previous study established that antioxidants supplementation preserve cellular thiols and maintains the cells integrity 26.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Therefore, pravastatin can protect the erythrocytes NPSH against primaquine induced oxidation. These findings are in agreement with the previous study established that antioxidants supplementation preserve cellular thiols and maintains the cells integrity 26.…”
Section: Discussionsupporting
confidence: 94%
“…These findings are in accordance with pervious study reported that in vitro exposure of RBCs to oxidants resulted in damaging of protein in addition to increase PCO formation 27. This may suggest that oxidant drugs increase free radicals production in red blood cells and decrease the activities of antioxidant enzymes 26. Furthermore, proteinases that protect erythrocytes proteins by degrading the oxidatively damaged proteins are lost during oxidative stress 28.…”
Section: Discussionmentioning
confidence: 99%
“…Malathion is usually dissolved in hydrocarbon solvents, and at present we cannot exclude the possible participation of methylbenzene (toluene) and trimethylbenzene in the reported effects, given that both are present in technical malathion used in the present work. Since it has been shown that toluene produces a number of deleterious biochemical and physiological effects [30][31][32], a synergistic effect could be partially responsible for reduction in antioxidant enzymatic activities. In an interesting work [33], it was shown that short-term treatment for 15-45 days, with a single daily dose of 650 mg ⁄ kg toluene, decreased GSH levels, GR and GPx activity demonstrating that cerebral cortex and cerebellum were the most affected tissues, while apoptosis and lipid peroxidation indices, as well as the glutathione disulphide, increased over treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Some researchers reported that toluene causes tissue damage by increasing the oxygen radicals [26, 27]. According to another hypothesis, toluene increases membrane fluidity by altering the lipid structure of the cell membrane and then affecting the Na/K-ATPase activity [6].…”
Section: Discussionmentioning
confidence: 99%